Empiric tranexamic acid use provides no benefit in urgent orthopedic surgery following injury. Issue 1 (10th March 2023) - Carr, Bryan; Li, Shi-Wen; Hill, Jamel G; Feizpour, Cyrus; Zarzaur, Ben L; Savage, Stephanie
Abstract : Background: Orthopedic literature has demonstrated a significant decrease in postoperative transfusion requirements when tranexamic acid (TXA) was given during elective joint arthroplasty. The purpose of this study was to evaluate the empiric use of TXA in semi-urgent orthopedic procedures following injury. We hypothesized that TXA would be associated with increased rates of venous thromboembolic events (VTE) and have no effect on transfusion requirements. Methods: Patients who empirically received TXA during a semi-urgent orthopedic surgery following injury (TXA+) were matched using propensity scoring to historical controls (CONTROL) who did not receive TXA. Outcomes included VTE within 6 months of injury and packed red blood cell utilization. Multivariable logistic regression and generalized linear modeling were used to determine odds of VTE and transfusion. Results: 200 patients were included in each group. There was no difference in mortality between groups. TXA+ patients did not have an increase in VTE events (OR 0.680, 95% CI 0.206 to 2.248). TXA+ patients had a significantly higher odds of being transfused during their hospital stay (OR 2.175, 95% CI 1.246 to 3.797) and during the index surgery (increased 0.95 units (SD 0.16), p<0.0001). Overall transfusion was also significantly higher in the TXA+ group (p=0.0021). Conclusion: Empiric use of TXA in semi-urgent orthopedic surgeries did not increase the odds of VTE. Despite the elective literature, TXA administration did not associate with less transfusion requirements. A properly powered, prospective, randomized trial should be designed to elucidate the risks and benefits associated with TXA use in this setting. Level of evidence: Level IV.